Permanent occurrence of Raphidiopsis raciborskii and cyanotoxins in a subtropical reservoir polluted by domestic effluents (Itupararanga reservoir, São Paulo, Brazil) - dos Santos Machado, Leila [UNESP]; Dörr, Fabiane; Dörr, Felipe Augusto; Frascareli, Daniele [UNESP]; Melo, Darllene S. [UNESP]; Gontijo, Erik S. J. [UNESP]; Friese, Kurt; Pinto, Ernani; Rosa, André Henrique [UNESP]; Pompêo, Marcelo M.; Moschini-Carlos, Viviane [UNESP] (Springer Nature, 2022)
Toxic cyanobacteria blooms are a frequent problem in subtropical reservoirs and freshwater systems. The purpose of this study was to investigate the occurrence of potentially toxic cyanobacteria and the environmental conditions associated with the presence of cyanotoxins in a Brazilian subtropical reservoir. Five collections were carried out at seven sampling locations in the reservoir, during the rainy and dry seasons, between the years 2016 and 2017. There was permanent occurrence of Raphidiopsis raciborskii (Woloszynska) Aguilera, Berrendero Gómez, Kastovsky, Echenique & Salerno (Phycologia 57(2):130–146, 2018), ranging between dominant and abundant, with an average biomass of 38.8 ± 29.9 mg L−1. Also abundant were Dolichospermum solitarium, D. planctonicum, Planktothrix isothrix, and Aphanizomenon gracile. Saxitoxin (STX) was detected in all the collected samples (0.11 ± 0.05 µg L−1). Microcystin (MC) was also detected, but at lower concentrations (0.01 ± 0.0 µg L−1). Low availability of NO3− and phosphorus limitation had significant effects on the R. raciborskii biomass and the levels of STX and MC. It was observed that R. raciborskii was sensitive to thermal stratification, at the same time that STX levels were higher. This suggested that STX was produced under conditions that restricted the growth of R. raciborskii. These are important findings, because they add information about the permanent occurrence of STX and R. raciborskii in an aquatic ecosystem limited by phosphorus, vulnerable to climatic variations, and polluted by domestic effluents.
Keywords: Aquatic ecosystem; Biomass; Blooms; Eutrophication; Microcystin; Saxitoxin